Design Aspects and Test of an Inductive Fault Current Limiter - Arsénio, Pedro; Vilhena, Nuno; Murta-Pina, João; Pronto, Anabela; Álvarez, Alfredo (Electrical, Control and Communication Engineering, 2014)
Magnetic shielding inductive fault current limiters with high temperature superconducting tapes are considered as emerging devices that provide technology for the advent of modern power grids. The development of such limiters requires magnetic iron cores and leads to several design challenges regarding the constitutive parts of the limiter, namely the primary and secondary windings. Preliminary tests in a laboratory scale prototype have been carried out considering an assembly designed for simplicity in which the optimization of the magnetic coupling between the primary and secondary was not the main focus. This work addresses the design configuration of an inductive current limiter prototype regarding the assembly of the primary and secondary windings in the core. The prototype is based on a closed magnetic core wound by a primary, built from a normal electric conductor, and a short-circuited secondary, built from first generation superconducting tape. Four different design configurations are considered. Through experimental tests, the performance of such prototype is discussed and compared, in terms of normal and fault operation regimes. The results show that all the configurations assure effective magnetic shielding at normal operation regime, however, at fault operation regime, there are differences among configurations.